Types of Penalties in the Sanction of Part 1 of the Article 296 of the Current Criminal Code of Ukraine: Non-Hidden Challenges with a Hidden Sense - Ya. H. Lyzohub (Bulletin of Kharkiv National University of Internal Affairs)
The author has studied the problem of incorrect legislative definition of the types of punishments in the sanction of Part 1 of the Art. 296 of the Criminal Code of Ukraine, which establishes criminal liability for hooliganism, from the point of view of some constitutive provisions of the General Part of the specified regulatory legal act.